Kezia Clarissa Langi STUDI LAPANGAN: TRADISI BAJU PERANG NIAS MASA KINI DI KOTA GUNUNGSITOLI DAN DESA BAWOMATALUO - Kezia Clarissa Langi; Setiawan Sabana; Hafiz Aziz Ahmad (PROSIDING: SENI, TEKNOLOGI, DAN MASYARAKAT, 2020)
For centuries the title ‘warrior’ is embedded in Nias society. As a warrior, the person, their duty, and its costumecannot be separated. To become the protector of a village, a series of task are needed. Therefore, being awarrior is a prestigious status. Today, Nias and its war costume are on the edge of modernity. The thin linebetween tradition and attraction is created due to globalization and its tourism purpose. To understand theimportance of the tradition of Nias war costume, it is crucial to analyze the history through literature and theimpact of globalization in Nias today. The result of this research could adapt into creating future Nias warcostume that is suitable for the Ono Niha (term for the people of Nias). To fully understand about the conditionof this tradition, field research is needed. This research aims to obtain data from Gunungsitoli city andBawomataluo village regarding the tradition of Nias war costume. The results of this research are the untoldstory of Nias and the needs of the society regarding Nias tradition in the future.